EDUKASI PERENCANAAN KEUANGAN KELUARGA MASYARAKAT ADAT DESA SUKAWATI PROVINSI BALI - Putu Yudy Wijaya; I Gede Putu Kawiana; I Gusti Ayu Suasthi; Ni Nyoman Reni Suasih (Universitas Mataram, 2022)
Knowledge of family financial management is very important to create a prosperous family. However, there are still families who have not compiled and planned family finances. Women in the family have an important role in managing the family economy. The needs of Balinese indigenous families are not only in the form of fulfilling basic needs (food, clothing, housing, health, education), but also the needs of religious rituals and customs. So that this community service targets mothers, with a locus in Sukawati Village. This activity aims to provide knowledge about planning and managing household finances, as well as helping to design and regulate household financial patterns for indigenous families in Sukawati Village. The method used in carrying out the activities consists of socialization or lectures on family financial management planning. The simulation was continued to prepare a family financial plan. This service activity was attended by 30 participants consisting of women from the coordinator of PKK in the Sukawati Village. Lectures or counseling activities on family financial planning for the Balinese indigenous people in Sukawati Village were initiated by giving material lectures. Next is the second stage with tutorials on the preparation of financial allocations, and the third stage is a discussion of family financial management issues. Based on the survey results after education and simulation were conducted, it was found that there was an increase in participants' knowledge and understanding of the financial management of indigenous peoples' families. A total of 93.33 percent of participants felt that this educational activity was useful, and the material presented by the implementation team showed that 80 percent of participants had understood the planning and preparation of family household finances. The activity participants have understood, and are able to prepare family financial and expenditure plans according to their respective sources of income and family needs.